Catching the liar as a matter of justice: Effects of belief in a just world on deception detection accuracy and the moderating role of mortality salience. (January 2015) - Schindler, Simon; Reinhard, Marc-André
Highlights: A strong belief in a just world has been linked to high interpersonal trust. This belief was assumed to imply low motivation to accurately detect deception. This belief was shown to be negatively linked to deception detection accuracy. Mortality salience was assumed to increase justice concerns among just world believers. Mortality salience was shown to increase detection accuracy among strong believers. Abstract: Belief in a just world has been linked to high interpersonal trust and less suspicion of deception. We therefore predicted people with a strong dispositional belief in a just world to have low motivation to accurately detect deception. Accordingly, we hypothesized such a belief to be negatively related to accuracy in deception detection. Furthermore, research on Terror Management Theory has indicated that culturally shared values, such as justice, become more important after mortality salience. Thus, we assumed engaging in justice concerns after a death threat is especially relevant for people with a strong belief in a just world, and further, that accurate deception detection is a matter of justice. Based on this reasoning, we expected people with a strong belief in a just world to have an increased motivation to accurately detect deception after mortality salience. Consequently, we hypothesized dispositional differences in belief in a just world to be unrelated to accuracy in deception detection after mortality salience. In line with these predictions, our study revealed that participants with a strong (vs. weak) belief in a just world were worse in deception detection unless they had first been reminded of their mortality.